2018
DOI: 10.1016/j.mad.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Altered ureteral contractility with ageing: Role of the rho-kinase pathway

Abstract: This study investigated the role of calcium sensitisation in the regulation of ureteral contractility with ageing. Isolated ureteral strips from young (6-month old) and older (3-year old) pigs were mounted in Krebs bicarbonate solution and contractility induced by the α1-adrenoceptor agonist phenylephrine (30 and 300 μM) and 5-HT (10 and 100 μM), recorded in the absence and presence of the rho-kinase inhibitors Y-27632 (10 μM) and fasudil (30 μM). Ureteral strips developed bursts of contractile activity which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
2
5
1
Order By: Relevance
“…We have previously reported that there are differences in contractions of the ureter in response to both α 1-adrenoceptor and 5-HT receptor stimulation (Lim, Chess-Williams, & Sellers, 2018b). The present results show that ureteral contraction in response to muscarinic receptor stimulation also differs in tissues from the two age groups.…”
Section: Discussionsupporting
confidence: 61%
“…We have previously reported that there are differences in contractions of the ureter in response to both α 1-adrenoceptor and 5-HT receptor stimulation (Lim, Chess-Williams, & Sellers, 2018b). The present results show that ureteral contraction in response to muscarinic receptor stimulation also differs in tissues from the two age groups.…”
Section: Discussionsupporting
confidence: 61%
“…5-HT-induced increase in the tension of isolated porcine intravesical ureters was reduced by 5-HT 2 and 5-HT 2A receptor antagonists, ritanserine and spiperone (Hernandez et al, 2003). The 5-HT 2 agonist, α-methyl-5HT, increased phasic contractions and overall contractile activity in isolated porcine distal ureter, which could be inhibited by the 5-HT 2 receptor antagonist, ketanserin (Lim, Chess-Williams & Sellers, 2018b). However, in human ureters, the role of 5-HT 2 has not been confirmed.…”
Section: Introductionmentioning
confidence: 90%
“…The vital role of 5-HT in the regulation of ureteral contraction has been revealed in ureteral preparations from different species. Enhanced ureteral contractions induced by 5-HT presented as increase in the frequency or elevated tension of phasic contractions have been observed in ureters from pigs (Hauser et al, 2002;Hernandez et al, 2003;Lim, Chess-Williams & Sellers, 2018b;Lim, Chess-Williams & Sellers, 2020) and humans (Gidener, Gumustekin & Kirkali, 1999;Gidener, Kirkali & Guven, 1995;Kuwahara, 1983;Long & Nergardh, 1978). However, no effects of 5-HT have been observed in canine and rabbit ureters (Borgstedt, Emmel & Benjamin, 1966;Yalcin et al, 2013), and no effects or dose-dependent effects (high doses inhibit and low doses excite) have been reported in rat ureters (Ancill, Jackson & Redfern, 1972).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous studies on the porcine distal ureter have shown that it is not possible to obtain reproducible concentration-response curves due to tachyphylaxis (Lim et al, 2018(Lim et al, , 2020.…”
Section: Effects Of E2 On 5-ht-induced Contractilitymentioning
confidence: 97%